1992
DOI: 10.1103/physreva.45.2416
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion in aqueous solutions of gelatin

Abstract: Dynamic-light-scattering experiments on semidilute aqueous solutions of gelatin indicate three relaxation processes: an exponential for times less than -50 psec followed by a power law at intermediate time and then a stretched exponential at long time. The characteristic time of the stretched exponential diverges as the system evolves to a gel. The latter two relaxations can be explained in terms of an anomalous diffusion mechanism where the mean-square displacement behaves as {R')-lnt at intermediate time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
89
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 28 publications
14
89
1
Order By: Relevance
“…This crossover property is found also in other many-body relaxation systems besides glass-formers [7,[56][57][58][59][60][61][62], and hence it is a general property. The magnitude of t c depends on the intermolecular potential V (r ).…”
Section: Guides From Experimentsmentioning
confidence: 55%
“…This crossover property is found also in other many-body relaxation systems besides glass-formers [7,[56][57][58][59][60][61][62], and hence it is a general property. The magnitude of t c depends on the intermolecular potential V (r ).…”
Section: Guides From Experimentsmentioning
confidence: 55%
“…[21] The interpretation of the q dependence of m seems to be very controversial. Ren et al [27,28] reported such behavior for aqueous gelatin solutions and gels and made an interpretation in the context with anomalous diffusion. They discussed this behavior in terms of a and b relaxation in glasses.…”
Section: Resultsmentioning
confidence: 99%
“…The values of a s are somewhat higher (2.5-3) than that of the fast relaxation mode. This behavior is usually attributed [19,[36][37][38] to internal motions of large association complexes. In view of experimental errors of a f and a s , we argue that the photochemical scission of the polymer chains has no significant effect on either the q-dependence of the fast or the slow mode.…”
Section: Resultsmentioning
confidence: 99%